Development and Implementation of a Novel Approach to Scaling the Meeting Centre Intervention for People Living with Dementia and Their Unpaid Carers, Using an Adapted Version of the Template for Intervention Description and Replication (TIDieR) Checklist - Nathan Stephens; Shirley Evans; Christopher Russell; Dawn Brooker (Behavioral Sciences)
Complex interventions are often poorly described, making it difficult to understand their development, implementation, and evaluation (i.e., context), which can aid in replicating and translating evidence into practice and policy. Therefore, we examined the development and implementation of an approach to scaling-out (increasing the numbers of) a psychosocial intervention for people affected by dementia across a rural county in England during 2019–2024. We used an adapted version of the TIDieR checklist to consider key items essential for replicating complex interventions at scale. We triangulated document analysis with interview data, and key programme stakeholders ratified the results of this study. We identified three programme components and sub-components, including how planned components were delivered, by whom, and under what conditions. Implementation outcomes related to the inner (e.g., top-down structure) and outer contexts (e.g., market failures) led to modifications that increased programme complexity. This study highlights the importance of programme leaders who can convene and drive systems and culture change to address implementation challenges, as well as the need for scaling science during programme development, for example, to determine optimal scale. Further research should include testing implementation outcomes to understand if the intervention is a scalable solution to the gap in post-diagnostic support in the UK.